Transcriptome-informed identification and characterization of Planococcus citri cis- and trans-isoprenyl diphosphate synthase genes - Mojca Juteršek; Iryna M. Gerasymenko; Marko Petek; Elisabeth Haumann; Sandra Vacas; Kalyani Kallam; Silvia Gianoglio; Vicente Navarro-Llopis; Michael Heethoff; Ismael Navarro Fuertes; Nicola Patron; Diego Orzáez; et al. (iScience, 2024)
Summary: Insect physiology and reproduction depend on several terpenoid compounds, whose biosynthesis is mainly unknown. One enigmatic group of insect monoterpenoids are mealybug sex pheromones, presumably resulting from the irregular coupling activity of unidentified isoprenyl diphosphate synthases (IDSs). Here, we performed a comprehensive search for IDS coding sequences of the pest mealybug Planococcus citri. We queried the available genomic and newly generated short- and long-read P. citri transcriptomic data and identified 18 putative IDS genes, whose phylogenetic analysis indicates several gene family expansion events. In vitro testing confirmed regular short-chain coupling activity with five gene products. With the candidate with highest IDS activity, we also detected low amounts of irregular coupling products, and determined amino acid residues important for chain-length preference and irregular coupling activity. This work therefore provides an important foundation for deciphering terpenoid biosynthesis in mealybugs, including the sex pheromone biosynthesis in P. citri.